Hubungan Regulasi Emosi dengan Resiliensi Akademik Siswa SMA Seminari Menengah Pematangsiantar - Mimpin Sembiring; Thomas Tarigan (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2022)
Emotion regulation is defined as the ability to control and manage individual emotions so that their emotions become stable. While academic resilience is the individual's capacity to face and overcome all problems, challenges, and obstacles to able to achieve success in studies. This study aims to determine the relationship between emotional regulation and student academic resilience. The subjects of this study were Pematangsiantar Middle School Seminary High School students, in 2021, totaling 218 people, starting from class X to class XII. The research instrument used was the student's academic resilience scale and the emotional regulation scale using a 4-option Likert scale. The data collected was first tested with validity and reliability tests, then normality was tested. The results of the validity test showed that the 16 items on the academic resilience scale got the lowest r value of 0.162> 0.1161 (r table). The 15 items of the emotional regulation scale got the lowest r table value of 0.403. Thus, all items from the two variables are declared valid. The results of the reliability test showed that Cronbach's alpha value on the emotion regulation scale was 0.878. Meanwhile, academic resilience is 0.894. Thus the reliability of each scale has been fulfilled. While the linearity test showed that the correlation between the variables X – Y was 0.00<0.05 with a df value of 0.024>0.05. It means thatvariable X has a significant and positive correlation with variable Y. Furthermore, the results of the regression analysis show that emotion regulation contributes 50.2% to students' academic resilience. It can be concluded that emotional regulation is a protective factor for the academic resilience of Pematangsiantar High School Seminary students.